Factors associated with the discontinuance of outpatient follow-up in neonatal units - Elysangela Dittz Duarte; Tatiana Silva Tavares; Isadora Virgínia Leopoldino Cardoso; Carolina Santiago Vieira; Bárbara Radieddine Guimarães; Mariana Bueno (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify predisposing and enabling factors as well as the health needs associated with the discontinuance of outpatient follow-up of newborns who were hospitalized at neonatal intensive care unit. Methods: cross-sectional study, using the behavioral model of health services use. The study was composed of 358 mothers and newborns referred to the outpatient follow-up after discharge. Characterization, perception of social support, postnatal depression, and attendance to appointments data were collected, analyzed by the R software (3.3.1). Results: outpatient follow-up was discontinued by 31.28% of children in the first year after discharge. In multiple regression analysis, the chance of discontinuance was higher for newborns who used mechanical ventilation (OR = 1.68; 95%CI 1.04-2.72) and depended on technology (OR = 3.54; 95%CI 1.32-9.5). Conclusions: predisposing factors were associated with the discontinuance of follow-up; enabling factors and health needs did not present a significant association. Children with more complex health conditions require additional support to participate in follow-up programs, thus ensuring the continuity of care.